Análisis y diseño del sistema para gestión administrativa de la Clínica Veterinaria " Dr. Bonilla" de la ciudad de Montalvo. - Arguello Zambrano, Washington Irving (2022)
This project focuses on the veterinary clinic of the City of Montalvo, which manually carries out the processes related to the medical history of patients, care and other information generated in the different areas of the clinic, which implies that the tasks inherent to the activity of clinical attention become limiting and do not allow its effective administration. The MySQL database and the PHP programming language that allow accessibility to interested parties such as veterinarians, administrators, laboratory technicians, interns and, above all, customers who access the system through any web browser. All the data of the clients and their pets with their medical records will be stored in a database and more precise searches can be made by entering the names of the patients or the main data of the owner. The client will be able to access the necessary information about their pets and will be able to view the necessary reports such as the vaccination and deworming certificate, with this it is about providing a tailored solution that meets the needs that arise in the veterinary clinic.